CHEMY SHOOTER GAME BASED COMPUTER AS INSTRUCTIONAL MEDIA ON ACID BASE FOR IMPROVE SELF-EFFICACY - Maissy Diana Rukmana; achmad lutfi (Universitas Negeri Surabaya, 2022)
This study aims to obtain the game as an acid-based learning media that can improve the self-efficacy skills of students of high school studentsusing the Chemy Shooter game as a learning media on acid-base materials with research and development (R&D) methods.The validation assessment results obtained 90,79% had fulfilled the validity category. The results of questionnaire responses and observations of students activities gained 96,16% and 93,33% with the category of very practical. Student learning outcomes significant values in the Kolmogorov-Smirnov normality test obtained a pretest value of 0,200 and posttest 0,200 so that it is greater than 0,05 so that it is normally distributed and Paired Sample t-Test test obtained significant pretest and posttest 0,000 significant values are less than 0,05 so that there are differences in the average pretest and posttest scores and the results of students self-efficacy skills gained 89,20% in the very effective category.